(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
No other linguistic subfield as closely linked to lexicography as etymology. Indeed, whilst significant work on synchronic lexicology is done without any reference to dictionaries, major etymological breakthroughs, be they factual or methodological, are mostly expressed through lexicographic work, and when they are not, it is their subsequent acceptance by a reference dictionary which ultimately lends them support.